A dual-channel visible light optical coherence tomography system enables wide-field, full-range, and shot-noise limited human retinal imaging - Wang, Jingyu; Nolen, Stephanie; Song, Weiye; Shao, Wenjun; Yi, Wei; Kashani, Amir; Yi, Ji (Communications engineering, 2024)
Visible light optical coherence tomography (VIS-OCT) is an emerging ophthalmic imaging method featuring ultrahigh depth resolution, retinal microvascular oximetry, and distinct scattering contrast in the visible spectral range. The clinical utility of VIS-OCT is hampered by the fundamental trade-off between the imaging depth range and axial resolution, which are determined by the spectral resolution and bandwidth, respectively. To address this trade-off, here we developed a dual-channel VIS-OCT system with three major advancements including the first linear-in-K VIS-OCT spectrometer to decrease the roll-off, reference pathlength modulation to expand the imaging depth range, and per-A-line noise cancellation to remove excess noise, Due to these unique designs, this system achieves 7.2 dB roll-off over the full 1.74 mm depth range (water) with shot-noise limited performance. The system uniquely enables >60° wide-field imaging which would allow simultaneous imaging of the peripheral retina and optic nerve head, as well as ultrahigh 1.3 µm depth resolution (water). Benefiting from the additional near-infrared (NIR) channel of the dual-channel design, this system is compatible with Doppler OCT and OCT angiography (OCTA). The comprehensive structure-function measurement enabled by this dual-channel VIS-OCT system is an advance towards adoption of VIS-OCT in clinical applications. Wang, Nolen and colleagues present an iteration of the existing visible light optical coherence tomography system, which improves both imaging depth, resolution and suppresses noise. The system was demonstrated in human retinal imaging.